Da voz do outro ao encontro de mundos : Gadamer, o multiculturalismo e o diálogo de culturas - Hammes, Itamar Luís (2012)
This doctoral dissertation deals with the contribution of Gadamer's philosophical hermeneutics to contemporary, ongoing debates on multiculturalism and the dialogue of cultures. Although Gadamer has not developed a political philosophy, he is often regarded as an author who contributed significantly to constructing an alternative account to multiculturalism or the dialogue of cultures. The question that guides the current research is as follows: Gadamer's philosophical hermeneutics, as a finite reflection is emancipated only in the encounter with the Other and to the extent that it holds that the deepening of self-understanding (Selbstverständnis) is attached to the understanding of other world views and life forms, can it be presented as a rational alternative to multiculturalism and the dialogue of cultures? The thesis presented here shows precisely that possibility. To the extent that he does not accept a relativistic idea of absolute incommensurability or incommunicability of the diverse world views and ways of life, and insofar as he defends a critical dialogue based on the art of asking questions and being open, Gadamer proposes a rationality that carries nearly universal standards for a dialogue of cultures or multiculturalism.